Spil, leg og idræt i nordisk middelalder - Søndergaard, Leif (Forum for Idræt, 1999)
Beskrivelse af de sociale klassers sportsdyrkelse og bevægelseskulturer i middelalderen i de nordiske lande. Games and Sports in the Middle Ages in the North From Saxo’s Gesta Danorum (ce. 1200), the Icelandic Sagas and the Norwegian King’s Mirror (ce. 1250), we obtain the clear impression that games and sports in the early Middle Ages served two main functions: 1) to display physical strength and 2) to train in the proper use of weapons. These abilities were needed at all levels of Viking and early medieval society. Even kings had to distinguish themselves in sports. Later in the Middle Ages sports and games were socially differentiated. The peasantry continued with trials of strength, – wrestling, boxing, tug-of-war, running and jumping games, ball games, throwing the javelin, shooting with longbow or crossbow, stone lifting etc. The nobility however developed new games. The chivalric virtues, values and norms were transmuted into tournaments. A full scale tournament comprised three sections: 1) riding at the ring, 2) fights between riding knights armed with lances and, 3) standing fights with swords. The nobles also played skittles and other games. The burghers in the towns invented their own games during the Later Middle Ages. Their guilds organised festive sports at Shrovetide, pulling the head off a goose, sword dancing, riding summer and winter, – and at Pentecost, shooting popinjays (a wooden figure on the end of a pole). During the Middle Ages sports and games lost most of their original function of displaying power. Instead they aspired to a place among the rituals of representative courtly display. The games were often integrated into annual festivities, and contributed to giving a distinct cultural identity to each of the social groups who performed them.